TEKNOLOGI TEPAT GUNA TEMPAT PEMBAKARAN SAMPAH RUMAH TANGGA DENGAN TANAH LIAT - -, Warsiyah (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Orchard Gondanglutung, Donoharjo, Ngaglik, Sleman, Yogyakarta represents a high population region with a lot of garbage that pollutes environment. The writer is very interested in handling the problem by doing this research entitled. The Incinerator of Domestic Garbage with Clay.The method used factor of efficiency of processing or wet garbage draining and dry garbage combustion and to the number of ash yielded and also combustion chamber by using proper technological appliance utilize the combustion of domestic garbage with clay. Result of research showed the highest combustion and draining efficiency were garbage with 0,5 kg weight with the combustion efficiency 92,06 %, while wet garbage with 3,5 kg weight combustion efficiency was 35,23%.From the research It can be concluded that the greater volume of garbage in the draining and combustion process will decrease combustion efficiency.